2001
DOI: 10.1101/gr.184401
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression Associated with Developmental Arrest and Longevity in Caenorhabditis elegans

Abstract: Gene expression in a developmentally arrested, long-lived dauer population of Caenorhabditis elegans was compared with a nondauer (mixed-stage) population by using serial analysis of gene expression (SAGE). Dauer (152,314) and nondauer (148,324) SAGE tags identified 11,130 of the predicted 19,100 C. elegans genes. Genes implicated previously in longevity were expressed abundantly in the dauer library, and new genes potentially important in dauer biology were discovered. Two thousand six hundred eighteen genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
188
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 47 publications
(40 reference statements)
17
188
2
1
Order By: Relevance
“…23 and F26E4.9, respectively) were found among the genes with increased transcripts in both dauer larvae and daf-2 adults. Elevated transcript abundance for cytochrome c oxidase subunits in dauer larvae was demonstrated earlier (Jones et al, 2001), but our observation also suggests a role for these genes in adult longevity. The average increase in expression for these genes was 2 to 6-fold (p < 0.001).…”
Section: Correlation Of the Sage Data With Differences In Longevitysupporting
confidence: 81%
See 2 more Smart Citations
“…23 and F26E4.9, respectively) were found among the genes with increased transcripts in both dauer larvae and daf-2 adults. Elevated transcript abundance for cytochrome c oxidase subunits in dauer larvae was demonstrated earlier (Jones et al, 2001), but our observation also suggests a role for these genes in adult longevity. The average increase in expression for these genes was 2 to 6-fold (p < 0.001).…”
Section: Correlation Of the Sage Data With Differences In Longevitysupporting
confidence: 81%
“…One of the libraries made from RNA extracted from two-day-old dauer larvae has been previously described (Holt and Riddle, 2003;Jones et al, 2001). The second dauer library was prepared from 2-week old dauer larvae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since dauer formation represents a metabolic response to resource limitation that is accompanied by increased longevity, it was suspected that dauerregulated genes could share some network properties with CR-regulated genes. Dauerregulated genes were identified based upon consistencies from two previous microarray experiments (Jones et al, 2001;Wang and Kim, 2003). In particular, 28 dauer-specific genes were identified by intersecting the 358 dauer-enriched genes found by Jones et al (2001) and 540 dauer-enriched genes found by Wang and Kim (2003).…”
Section: Invertebrate Models Of Crmentioning
confidence: 99%
“…Dauerregulated genes were identified based upon consistencies from two previous microarray experiments (Jones et al, 2001;Wang and Kim, 2003). In particular, 28 dauer-specific genes were identified by intersecting the 358 dauer-enriched genes found by Jones et al (2001) and 540 dauer-enriched genes found by Wang and Kim (2003). Likewise, 40 nondauer-specfic genes were identified by intersecting the 533 nondauer-specific genes found by Jones et al (2001) and 1984 genes induced during dauer recovery in the study of Wang and Kim (2003).…”
Section: Invertebrate Models Of Crmentioning
confidence: 99%